Decadal-Scale Trends in Size of Mature Female Atlantic Blue Crab Callinectes sapidus in Estuarine and Nearshore Waters of the Southeastern US - Michael Thienes; Tracey Smart; Jeff F. Brunson; Michael R. Kendrick (Estuaries and Coasts, 2025)

Black Sea Bass Centropristis striata Year Class Strength and Spatial Extent from Two Long-Term Surveys off the Southeast U.S. Atlantic Coast - Julie L. Vecchio; Margaret W. Finch; Kevin R. Spanik; Amy Zimney; Tracey I. Smart (Fishes, 2025)
The Southeastern U.S. Atlantic coast (North Carolina to Florida, U.S.A.) has undergone considerable environmental change in recent decades, including increasing coastal water temperature and human development. The region is also home to a diverse suite of exploited reef fish species, including the southern stock of black sea bass (Centropristis striata). The objective of the current study was to compare trends in black sea bass year class strength and central location captured by trawls (age 0) and traps (age 2) as well as compare those trends to regional bottom temperature. We found no correlation between age 0 and age 2 abundance when comparing the same year class, suggesting that the numbers of trawl-caught juveniles cannot predict the number of adults available to the fishery. Larger year classes observed in traps were correlated with centers of abundance farther south in the region, while smaller year classes corresponded with more northerly centers of abundance. In both trawls and traps, strong year classes occurred following years with below-average regional water temperatures, and a series of recent, weak year classes correspond with recent higher-than-average water temperatures. It is unclear whether correlations between shifting centers of abundance, year class strength, and regional bottom temperature indicate a range contraction for the southern stock of black sea bass or movement into areas previously inhabited by the northern stock of the species.

Increased fishery-independent sampling effort results in improved population estimates for multiple target species - Julie L. Vecchio; Walter J. Bubley; Tracey I. Smart (Frontiers in Marine Science, 2023)
The power of fishery-independent surveys for stock assessments and management decisions is in their consistency over time and space. Although the preference is to limit change to survey execution, such changes may be necessary. In multi-species surveys, changes that improve metrics for one species may be a detriment to survey performance for others. In 2010, the Southeast Reef Fish Survey (SERFS) was formed to better address sampling needs off the U.S. Southeast Atlantic coast by intensifying a historical chevron trap survey (MARMAP), especially at the northern and southern extent of the sampling range. We used several performance metrics (encounter rate, annual coefficient of variability, standard error, and relative abundance index values) to determine the impact of this change in survey coverage on trend estimates for three commonly encountered species with varying centers of distribution in the survey region. Gray Triggerfish ( Balistes capriscus ) is found throughout the range of both surveys (i.e. centrally-distributed), while White Grunt ( Haemulon plumierii ) and Red Snapper ( Lutjanus campechanus ) are centered near the northern and southern extent of the sampling range, respectively. For Gray Triggerfish, the survey intensification had no effect on encounter rate, but reduced the coefficient of variation and indicated that the historical index of relative abundance may have been overestimated. For White Grunt, the survey intensification slightly improved CV but did not affect the index of relative abundance value or encounter rate. For Red Snapper, SERFS increased encounter rates, reduced CV overall, and detected a population increase 5 years earlier than MARMAP. Overall, the intensification of the survey improved at least one performance metric for each species and showed few deleterious effects on performance, suggesting that intensification of the survey was a net-positive for the accurate estimation of population trends in several species of interest.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Multi-decadal decline in reef fish abundance and species richness in the southeast USA assessed by standardized trap catches - Nathan M. Bacheler; Tracey I. Smart (Marine Biology, 2016)

Environmental cues and seasonal reproduction in a temperate estuary: a case study of Owenia collaris (Annelida: Polychaeta, Oweniidae) - Tracey I. Smart; Craig M. Young; Richard B. Emlet (Marine Ecology, 2012)
Coordination of gametogenesis and spawning during restricted breeding seasons increases availability of mates, fertilization rates, and often success of offspring. Orton’s Rule predicts water temperature as the dominant environmental cue for gametogenesis or spawning in temperate invertebrates. Crisp’s Rule predicts that species producing planktotrophic larvae will time their reproduction to ensure optimal nutrition for the larvae. Owenia collaris (Annelida: Oweniidae) is a temperate polychaete that produces planktotrophic larvae that remain in the water column for several weeks. Reproductive phenology and its relationship to the environment were investigated in an estuarine population of O. collaris using field and laboratory studies. Owenia collaris produced mature gametes between March and September each year during the productive season between the spring and fall transitions when day lengths were 12 h or more, alkalinity was 8.1 or higher, and temperature was 11 °C or higher. Gamete production was not related to seasonal changes in salinity or benthic phytoplankton concentrations and gametes were present prior to the spring phytoplankton bloom. In laboratory experiments, production of gametes was influenced somewhat by manipulating day lengths but not adult food. The association with predictable and stable environmental cycles (day length) and a broad spawning season suggest that this species is unlikely to mis‐match with larval food availability which would lead to reduced availability of recruits in any given year, supporting Crisp’s Rule. Our data do not support the hypothesis that reproductive timing in this species is driven by access to excess energy required by adults to initiate the production of gametes. Our data also do not support Orton’s premise that temperature is the primary controlling factor of reproduction in this temperate marine invertebrate.

Spawning and development in Osedax boneworms (Siboglinidae, Annelida) - Greg W. Rouse; Nerida G. Wilson; Shana K. Goffredi; Shannon B. Johnson; Tracey Smart; Chad Widmer; Craig M. Young; Robert C. Vrijenhoek (Marine Biology, 2009)

Clinical Relevance of Dissolution Testing in Quality by Design - Paul A. Dickinson; Wang Wang Lee; Paul W. Stott; Andy I. Townsend; John P. Smart; Parviz Ghahramani; Tracey Hammett; Linda Billett; Sheena Behn; Ryan C. Gibb; Bertil Abrahamsson (The AAPS Journal, 2008)